(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The analysis of the manufacture of plastic details of the oil-field equipment was made, which made it possible to establish the regularity of the shrinkage change of plastic details from the regimes of their production. Changes of quality of ready details depending on casting pressure are defined, and the regularity of the change in shrinkage, density, ruggedness, hardness, breaking stress at distension from regimes of casting is established.